O acolhimento familiar como garantia do direito à convivência familiar e comunitária - Valente, Janete Aparecida Giorgetti (2008)
Brazil has a history of 500 years of institutionalization of children and adolescents. Since 1990, with the implantation of the Child and Adolescent Statute, a constant effort has been effectuated to guarantee the right to family and community life to this segment. The importance of family and community life for children and adolescents is recognized in the Federal Constitution and in the Child and Adolescent Statute, as well as in other national and international regulations. An important and democratic proposal has been introduced in Brazil in 2006, with a broad participation of national segments: the National Plan for the Promotion, Protection and Defense of the Right of Children and Adolescents to Family and Community Life. This Plan proposes to prioritize this theme, motivating the conceptualization and implementation of public policies to ensure this right, constituting a landmark to the standing up to the culture of institutionalization of children and adolescents in Brazil. Some initiatives of family fostering attempt to offer care alternatives to children and adolescents that need to be temporarily separated from their families. There are also municipalities that have set forth, as a public policy, a Foster Family Program, as the alternative for children and adolescents in need of this kind of protection. This analysis is an offspring of the experience of the SAPECA Program, run by the Municipal Secretary of Social Assistance of the Municipal Administration of Campinas, SP. SAPECA is a family assignation program defined by Art. 90 of the Child and Adolescent Statute, and its objective is to assist in foster families children and adolescents victimized by domestic violence, offering vitalization conditions for their family and community networks, with possibilities of access to social services networks and psychological and social counseling for the family and community groups